1990
DOI: 10.1111/j.1600-051x.1990.tb01097.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of autologous fibronectin in the surgical repair of through‐and‐through furcation lesions in man A pilot study

Abstract: 4 subjects with bilateral through-and-through mandibular furcation lesions were assessed for the healing response in terms of attachment gain following surgical debridement, root planing, citric acid demineralisation and topical application of autologous fibronectin. The results were compared with sham-operated and saline-treated contra-lateral sites. There was no significant difference in the attachment gain at sites treated with autologous fibronectin and citric acid compared with sites treated with citric a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Thirty‐four articles were excluded after full‐text review (Table 3). 10‐12,16,30‐59 A final selection of 150 articles was made, of which six were systematic reviews, 2,60‐64 109 were clinical trials, 53,65‐172 27 were case series, 173‐199 and eight were case reports 200‐207 . No cohort studies were identified.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Thirty‐four articles were excluded after full‐text review (Table 3). 10‐12,16,30‐59 A final selection of 150 articles was made, of which six were systematic reviews, 2,60‐64 109 were clinical trials, 53,65‐172 27 were case series, 173‐199 and eight were case reports 200‐207 . No cohort studies were identified.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 24 clinical trials 149‐172 and 13 case series 185‐197 were non‐classifiable, as defined in Materials and Methods (Tables 4 and 5). Of the 85 remaining clinical trials, 53,65‐148 eight reported outcomes after applying regenerative therapy on maxillary facial/interproximal Class II furcation defects, 76,87,92,100,105,140,148,208 68 on mandibular facial/lingual Class II furcation defects, 65‐68,70‐72,75,77,78,80‐85,87‐90,93‐99,101‐104,106,107,110‐112,114‐122,124‐139,141‐147 one on maxillary Class III furcation defects, 91 nine on mandibular Class III furcation defects, 69,73,74,77,86,108,109,113,123 and one on maxillary premolars presenting Class I and Class II furcation defects 79 . Of the 14 selected case series, two reported on the treatment of maxillary facial/interproximal Class II furcation defects, 177,180 11 on mandibular facial/lingual Class II furcation defects, 173‐176,178‐184 and two on mandibular Class III furcation defects 198,199 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations